Web Based Model of a Digital Fax Document Management System - Aida Rosmiza, Shuib (2009)
The Government of Malaysia has encouraged the use of Information Technology application among the public and private sector to enable both sectors to compete and provide better facilities. Most brick and mortar or physically located organizations also seek alternatives for handling the document management. Nowadays, most of the information in the organization is stored in unstructured manner that require certain technique to be applied in order to retrieve the important and relevant information from a large scale of collected data. A digital document management system takes advantage of advanced document analysis and management techniques. In this study, a document from the fax machine that is a structured data is used in the system to digitalize the fax documents into the document management system.